PENDAPATAN DAN KESEJAHTERAAN RUMAH TANGGA PETANI UBI KAYU DI KECAMATAN SUKADANA KABUPATEN LAMPUNG TIMUR - Agum Muhammad Iqbal; Dyah Aring Hepiana Lestari; Achdiansyah Soelaiman (Lampung University, 2014)
The purpose of this study was to analyze the cassava farm income, determine the amount of household income of cassava farmers, determine the level of welfare of households by household expenditure cassava farmers. The study was conducted using a survey method in District Sukadana, East Lampung regency. The location was conducted in Sukadana District, and it was selected purposively. Respondents were 48 cassava farmers drawn using simple random sampling method. Data were analyzed qualitatively and quantitatively. The results showed that average income of cassava farmers based on cash costs and total cost of Rp 21,931,956.9/year and USD 20,795,322,09/th per hectare. This Farming was beneficial because it gained acceptance ratio and the ratio obtained over and above the total cash cost (R/C ratio) of 4.71 and 3.95. Average household income of cassava farmers was Rp27,126,481.25 / years. Sajogyo criteria, there were 38 farm household were classified as peasants and 18 of them were classified as simple household. Keywords: Cassava, expenditures, household welfare income